Building the concept for WHO Evidence Considerations for Vaccine Policy (ECVP): Tuberculosis vaccines intended for adults and adolescents as a test case. Issue 12 (15th March 2022) - Kochhar, Sonali; Barreira, Draurio; Beattie, Pauline; Cavaleri, Marco; Cravioto, Alejandro; Frick, Mike W.; Ginsberg, Ann M.; Hudson, Ian; Kaslow, David C.; Kurtz, Sherry; Lienhardt, Christian; Madhi, Shabir A.; et al.
Abstract: Currently, no formal mechanisms or systematic approaches exist to inform developers of new vaccines of the evidence anticipated to facilitate global policy recommendations, before a vaccine candidate approaches regulatory approval at the end of pre-licensure efficacy studies. Consequently, significant delays may result in vaccine introduction and uptake, while post-licensure data are generated to support a definitive policy decision. To address the uncertainties of the evidence-to-recommendation data needs and to mitigate the risk of delays between vaccine recommendation and use, WHO is evaluating the need for and value of a new strategic alignment tool: Evidence Considerations for Vaccine Policy (ECVP). EVCPs aim to fill a critical current gap by providing early (pre-phase 3 study design) information on the anticipated clinical trial and observational data or evidence that could support WHO and/or policy decision making for new vaccines in priority disease areas. The intent of ECVPs is to inform vaccine developers, funders, and other key stakeholders, facilitating stakeholder alignment in their strategic planning for late stage vaccine development. While ECVPs are envisaged as a tool to support dialogue on evidence needs between regulators and policy makers at the national, regional and global level, development of an ECVP will not preclude or supersede the independent WHO's Strategic Advisory Group of Experts on Immunization (SAGE) evidence to recommendation (EtR) process that is required for all vaccines seeking WHO policy recommendation. Tuberculosis (TB) vaccine candidates intended for use in the adolescent and adult target populations comprise a portfolio of priority vaccines in late-stage clinical development. As such, TB vaccines intended for use in this target population provide a 'test case' to further develop the ECVP concept, and develop the first WHO ECVP considerations guidance.